Effects of Using Pumice Sand as A Partial Replacement of Fine Aggregate in Lightweight Concrete Mixtures - Abdul Gaus; Mufti Amir Sultan; Raudha Hakim; Ichsan Rauf (LPPM of NAROTAMA UNIVERSITY, 2022)
Purpose: The advantage of lightweight concrete is to reduce the weight, which is considered the dead load on the structure. This study aims to determine the effect of replacing sand with pumice sand as fine aggregate in lightweight concrete. The substitution affects the compressive strength, split tensile strength, and weight. Design/methodology/approach: The research method is through testing in the laboratory, where the test specimens are cylindrical following SNI with a height of 30 cm and a diameter of 15 cm totaling 50 pieces. The composition ratio between regular and pumice sand is 75%:25%, 50%:50%, 25%:75%, and 0%:100%, respectively. Control of the test object using 100% regular sand. Findings: This research shows that adding pumice sand into the mixture decreases the volume weight. The weight of the volume of concrete produced is < 1,900 kg/m3, which is classified as a lightweight one. Research limitations/implications: The resulting compressive strength of 56.63 kg/cm2 decreased against the control test object by 81.10%. At the same time, the split tensile strength is 1.13 kg/cm2, or a decline of 52.05% from the control test object. Originality/value: This paper is an original work. Paper type: Research paper